A randomised control trial comparing the use of prefabricated orthotics in combination with orthotic sandals versus the sole use of prefabricated orthotics for the treatment of plantar fasciitis - Ampat, George; Rhodes, Samantha; Sims, Jonathan; Madathilethu, Jaida Chacko (International Journal of Clinical Trials, 2022)
Background: Plantar fasciitis is a painful and debilitating condition. There is currently no standard treatment for plantar fasciitis. Literature has shown that foot orthotics can help decrease pain and improve foot function in patients with plantar fasciitis. Orthotic sandals have also been shown to reduce symptoms of plantar fasciitis. These devices have only been used independently. This study will aim to take a novel approach to combine the orthotic and orthotic sandal to investigate the effect on plantar fasciitis symptoms. Methods: A total of 104 participants will be randomised into two groups. Participants in group A, the test group, will be provided with prefabricated orthotics and indoor orthotic sandals, and participants in group B, the control group, will only be provided with prefabricated orthotics. Outcome data will be collected five times over a period of six months. The primary outcome measure of change in pain over time will be measured with the Visual analogue scale. The secondary outcome measures of changes in foot health status and overall health will be measured using the Foot health status questionnaire and Global rating scale of change, respectively. Conclusions: The combined use of orthotics and orthotic sandals will increase the amount of time that the foot has adequate support. This novel research aims to provide evidence for an effective and easily implemented, standardised treatment for plantar fasciitis. Trial Registration: This trial was registered in May 2021 (NCT04894383).